Gender dan Tingkat Nyeri Dismenore: Apakah Dukungan Sosial dan Kecemasan Ikut Berpengaruh? - Aulia Afriany (AN-NISA, 2019)
Gender and Pain Levels of Dysmenorrhea: Does Social Support and Anxiety Also Influence?Dysmenorrhea is a menstrual disorder characterized by pain that attacks the lower abdomen until it reaches the pelvic area and thighs, which is experienced by individuals before and during menstruation due to muscle contractions in the uterine lining that block bloods flow. Dysmenorrhea is a common health problem in society that affects the quality of life of individuals. Physical and psychological factors of pain sufferers also contribute to influencing the level of dysmenorrhea pain. This study aims to determine the relationship between social support and anxiety with the level of adolescent pain in SMA Negeri 16 Makassar. Subjects in this study were 150 people consisting of young women aged 15 to 17 years who were known to have experienced menarche for at least one year and had not experienced menopause, lived with parents, and were known to have dysmenorrhea. Data collection was carried out on adolescents in Makassar 16 Public High Schools by using social support scale, depression, anxiety, and stress scale (DASS) scale and pain comparison scale. Data analysis uses multiple regression analysis techniques. The results show the value of P = 0.007, R-square = 0.064, and Fcount = 5.065. The analysis showed that social support and anxiety together had an influence on the level of dysmenorrhea pain in adolescents at SMA Negeri 16 Makassar (Fcount> Ftable = 5.065> 3.00). The effective contribution of social support and anxiety to the level of pain is 6.4%. These results indicate that social support and anxiety have a low influence on pain levels.Â AbstrakDismenore merupakan gangguan menstruasi yang ditandai dengan rasa sakit yang menyerang perut bagian bawah hingga mencapai daerah panggul dan paha, yang dialami individu sebelum dan sesaat menstruasi karena kontraksi otot pada dinding rahim yang menghambat aliran darah. Dismenore menjadi masalah kesehatan umum di masyarakat yang mempengaruhi kualitas hidup individu. Faktor fisik dan psikologis penderita nyeri turut andil dalam mempengaruhi tingkat nyeri dismenore. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial dan kecemasan dengan tingkat nyeri remaja di SMA Negeri 16 Makassar. Subjek dalam penelitian ini adalah 150 orang yang terdiri dari remaja putri berusia 15 sampai 17 tahun yang diketahui telah mengalami menarche minimal satu tahun dan belum mengalami menopause, tinggal bersama orang tua, dan diketahui mengalami dismenore. Pengumpulan data dilakukan terhadap remaja di SMA Negeri 16 Makassar dengan menggunakan skala dukungan sosial, skala depression, anxiety, and stress scale (DASS) dan skala perbandingan nyeri. Analisis data menggunakan teknik analisis regresi ganda. Hasil menunjukkan nilai P=0,007, R-square=0,064, dan Fhitung=5,065. Hasil analisis menunjukkan bahwa dukungan sosial dan kecemasan bersama-sama memiliki pengaruh terhadap tingkat nyeri dismenore pada remaja di SMA Negeri 16 Makassar (Fhitung > Ftabel = 5,065 > 3,00). Besar sumbangsih efektif dukungan sosial dan kecemasan terhadap tingkat nyeri adalah sebesar 6,4%. Hasil tersebut menunjukkan bahwa dukungan sosial dan kecemasan memiliki pengaruh yang rendah terhadap tingkat nyeri.